Maux de l'étranger. Mots de l'étrangeté dans Summertime de J.M. Coetzee - Cécile Birks (Revue LISA)
Written in 2009, J.M.Coetzee’s Summertime examines the modalities and intricacies of the personal itinerary of a white male writer in the making, a Mr John Coetzee, and the maturation of a literary oeuvre in the heyday of apartheid. This multifaceted text focuses on John's formative years and J.M. Coetzee's fictional protagonist stands out not only as an outsider but also as a melancholy philologist caught up in a profoundly estranged relationship with the languages he had been brought up in and had to speak and work with, and, subsequently, with his culture, family and lovers. Coetzee's text overtly discusses the complex political and ideological framework that shaped, stifled and fractured the society and culture his protagonist had grown up in and away from but also to some extent the geographical, sociological, racial and linguistic transformations that had started to take place underground and against the apartheid regulations and oppression.